Structural Damping of Mechanical Vibration - Vašina, Martin; Hružík, Lumír; Bureček, Adam (Manufacturing Technology Journal, 2016)
Mechanical vibration is undesirable in the majority of cases. It can have a negative influence on accuracy of manufacture, service life of processing equipment and tools, labour protection, human health and so on. Excessive noise belongs to the accompanying phenomena of the mechanical vibration too. For these reasons it is necessary to eliminate mechanical vibration in an appropriate manner. There are different possibilities of vibration damping. Application of suitable materials with damping effects belongs to these possibilities. This paper is focused on structural damping of materials. Damping properties of different materials were experimentally measured and subsequently evaluated by means of the forced oscillation method. It was found that the vibration damping depends not only on the material type but also on material density and thickness, excitation frequency and mass load.
Keywords: Forced Oscillation; Transfer Damping Function; Frequency; Thickness; Inertia Mass